Handbook of Research on Digital Innovation and Networking in Post-Covid-19 Organizations - Pego, Ana; Pego, Ana, 1969- (USA: IGI Global, 2022)
"This book of research chapters highlight the broad potential and adaptation that organizations faced during the Covid-19 crisis of the past few years"--
Includes bibliographical references and index.
Keywords: Technological innovations; Business networks -- Management; COVID-19 Pandemic, 2020 -- Influence